Improving Management of Hyperthermia on Children Under 5 Years Comparative Study on Highest 3 Cases in Agricultural Area - Lantin Sulistyorini; Nuning Dwi Merina; Peni Perdani Juliningrum; Ira Rahmawati; Aufa Azizah; Izdihar Javier Wardika (Universitas Jember, 2023)
Fever is the most common problem in children Giving antipyretics to treat fever gives a topical reaction and causes discomfort in children when they have a fever. Tepid sponge as a method of reducing temperature by administering water to the surface of the patient's skin to control body temperature based on the principles of evaporation and conduction of body temperature can cause comfort in children. The purpose of this study was to determine the effect of tepid sponge on decreasing body temperature in pediatric patients with ARI, diarrhea and seizures. The research design was a two group pretest-post-test design (tepid sponge) as the treatment given to the patients under five with ARI, diarrhea and febrile seizures in the inpatient room of RSD dr. Soebandi Jember and RSD dr. Abdoer Rahem Situbondo. 60 participants were involved as the sample of the study selected through purposive sampling. The results were analyzed using the Wilcoxon Sign Rank test with a significance level was set at α = 0.05. Tepid Sponge is effective for reducing body temperature in children. Nurses, families and parents can safely apply the Tepid Sponge as a hyperthermia management solution for pediatric patients.